Density, calorific value and cleavage strength of selected hybrid Eucalypts grown in uganda - Turinawe, Harold; Mugabi, Paul; Tweheyo, Mnason (Maderas. Ciencia y Tecnología, 2015)
This study was done to ascertain the suitability of Uganda’s clonal eucalypts for fuelwood. The objectives were to determine: (i) basic density (BD); (ii) calorific value (CV); and (iii) cleavage resistance (CLR) parallel to the grain of widely adopted clones i.e. GU7, GU8, GC540, GC550 and GC796 and to compare these properties with those of their parent materials; i.e. Eucalyptus grandis, Eucalyptus cammaldulensis, and Eucalyptus urophylla. Tests were done according to BS373(1957) and ASTM:E870-82(2006) procedures. Clone GC540 showed the highest BD (664kg/m3), GU7 had the highest CV (17800kJ/kg), GU7 and GC540 had higher values for CLR (20N/mm). BD and CLR means were in-between parent material means for GC clones. All clones had lower values of CV compared to parent materials. It was concluded that clonal wood at 6-7 years remains a viable alternative for fuelwood due to high volume increment per unit time and moderate CLR values to allow ease of splitting.